Identifying English Needs and Challenges for Angklung and Bamboo Music Programs - Denhaz Nurul Hakim; Hinhin Agung Daryana (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to identify the needs and challenges of English language learning as a key component of musical communication in the internationally recognized context of angklung and bamboo music. The needs analysis focuses on four themes: contextual musical needs, challenges specific to the music context, psychosocial influences, and relevant teaching strategies. The study employs a qualitative case study design using purposive sampling. Data were collected through three techniques: interviews with three music lecturers based on their expertise, classroom observations, and analysis of relevant documents. The data were analyzed using a six-stage qualitative analysis process. The findings reveal that current English instruction is not fully contextualized or applicable to the communicative needs of music, both spoken and written. Key challenges include limited academic writing skills and the insufficient integration of traditional music vocabulary with English. Student-related internal factors, such as lack of discipline and responsibility, also hinder the learning process. However, learning strategies that are engaging and aligned with musical practice can enhance students' English proficiency. Future research should focus more specifically on angklung and bamboo music contexts, including the development of appropriate teaching methods, standardized interactive angklung templates, and a glossary of traditional music terms with accurate English equivalents.